Time Series Data Mining with an Application to the Measurement of Underwriting Cycles. Issue 3 (3rd July 2019) - Owadally, Iqbal; Zhou, Feng; Otunba, Rasaq; Lin, Jessica; Wright, Douglas
Abstract : Underwriting cycles are believed to pose a risk management challenge to property-casualty insurers. The classical statistical methods that are used to model these cycles and to estimate their length assume linearity and give inconclusive results. Instead, we propose to use novel time series data Mining algorithms to detect and estimate periodicity on U.S. property-casualty insurance markets. These algorithms are in increasing use in data science and are applied to Big Data. We describe several such algorithms and focus on two periodicity detection schemes. Estimates of cycle periods on industry-wide loss ratios, for all lines combined and for four specific lines, are provided. One of the methods appears to be robust to trends and to outliers.